IJCM_158A: Usage and disposal of plastic waste among general population in urban slums of Field practice area, Gandhi medical college, Telangana. - Jatoth Madhavi DR; Sushmitha T.; Koteswaramma CH (Wolters Kluwer Medknow Publications, 2024)
Background: Plastics, owing to their ease of use and affordability, have taken over every aspect of our modern world. It has become an essential aspect of our everyday lives, permeating every sector from food packaging to toys and electronics, to the degree that it is unimaginable to picture a world without it. Plastic takes around 15 to 1000 years to biodegrade. The consumption of plastic by individuals and the ineffective reuse or recycling of it has detrimental effects on the ecosysystem. Overusing plastic and neglecting disposal solutions for plastic over a long time led not only India but many other nations to adopt laws to limit plastic because of its increasing environmental damage. Objectives: 1. To determine the utilization and disposal of plastic waste among general population in urban slums. 2. To study association between sociodemographic factors and plastic usage and disposal. Methodology: Study Design: A cross sectional analytical study Study Population: General population residing in urban slum Sampling Technique: Simple random sampling Sample Size:216 (p= 50%, l= 7, NR=10%) Study Tools: Self-designed, semi structured, pilot-tested questionnaire will be used for the data collection which will be entered in Microsoft Excel and analysed using SPSS statistical software version 20. Results: Usage of plastic was seen in all the study participants and more than 96% of them were reusing the plastics more than once. Most common method was disposing plastic in municipal dust bins (60.2%) followed by open dumping (20.9%), whereas 16.4% were reusing them for other purposes. Level of education and religion has no association with proper disposal of plastic waste. Present study observed that there was a significantly high percentage (96.1%) of three generation families were following proper plastic waste disposal methods followed by nuclear and Joint families with 56.9% and 48.8% respectively. with P≤0.05. Conclusion: Most common method was disposing plastic in municipal dust bins followed by open dumping. Level of education and religion has no association with proper disposal of plastic waste.